2011
DOI: 10.1111/j.2042-3306.2010.00325.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of p63, a regulator of epidermal stem cells, in the chronic laminitic equine hoof

Abstract: SummaryReasons for performing study: Abnormal epidermal stem cell regulation may contribute to the pathogenesis of equine chronic laminitis. Objective: To analyse the involvement of p63, a regulator of epidermal stem cell proliferative potential, in chronic laminitis. Methods: Epidermal tissues from skin, coronet and lamellae of the dorsal foot were harvested from 5 horses with chronic laminitis and 5 control horses. Tissues were analysed using histopathology, immunofluorescence microscopy and quantitative imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
35
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 26 publications
6
35
1
Order By: Relevance
“…It has been reported that more than 60% of isolated human corneal and limbal epithelial cells were positive for this marker [62]. Unlike previous findings in horse skin [63], it should be mentioned that in this study, using a rabbit polyclonal antibody directed to a mix of p63 isoforms, the expression of p63 was not restricted to the nucleus. Immunoblotting analyses later confirmed crossreactivity of the antibody with our equine EpSCs.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…It has been reported that more than 60% of isolated human corneal and limbal epithelial cells were positive for this marker [62]. Unlike previous findings in horse skin [63], it should be mentioned that in this study, using a rabbit polyclonal antibody directed to a mix of p63 isoforms, the expression of p63 was not restricted to the nucleus. Immunoblotting analyses later confirmed crossreactivity of the antibody with our equine EpSCs.…”
Section: Discussioncontrasting
confidence: 77%
“…Dilution optimization, as well as isotype and positive controls further validated these results, revealing cytoplasmic localization (data not shown). By contrast, Carter et al described strictly nuclear signals using mouse monoclonal antibodies directed to the delta N region of the peptide in equine skin samples [63]. It is likely that the noted discrepancies in cellular localization associated with the different antibodies arise from the differences in epitope specificity.…”
Section: Discussionmentioning
confidence: 95%
“…Indeed, p63-null mice display severe defects in epithelial development (Mills et al, 1999;Yang et al, 1999). Genetic studies suggest that mutations in p63 contribute to the pathogenesis of a wide range of ectodermal dysplasias (EDs), characterized by ectodermal malformations and hypoplasias (Celli et al, 1999;Koster, 2010;Rinne et al, 2007;van Bokhoven and McKeon, 2002), and we have recently noted decreased p63 expression in chronic equine laminitis in which the proliferative epidermal layers appear dysplastic (Carter et al, 2011). Thus, it is clear that p63 plays a key role in both the normal physiology and pathophysiology of the epidermis.…”
Section: Introductionmentioning
confidence: 99%
“…The chronic phase of laminitis is characterized by inadequate tissue healing and aberrant regenerative responses that result in lamellar hyperplasia and dysplasia, which correspond to the gross lesion of a lamellar wedge. 5,9,26 Horses with chronic laminitis and lamellar wedge formation often develop radiographically evident changes in the DP, such as bone remodeling and fractures along the solar margin, whereas in acute stages of laminitis, bone lesions are difficult to detect with routine imaging modalities. …”
mentioning
confidence: 99%
“…The chronic phase of laminitis is characterized by inadequate tissue healing and aberrant regenerative responses that result in lamellar hyperplasia and dysplasia, which correspond to the gross lesion of a lamellar wedge. 5,9,26 Horses with chronic laminitis and lamellar wedge formation often develop radiographically evident changes in the DP, such as bone remodeling and fractures along the solar margin, whereas in acute stages of laminitis, bone lesions are difficult to detect with routine imaging modalities. 2,30,34,42 Although magnetic resonance imaging of feet from horses with acute and chronic laminitis has identified evidence of DP bone remodeling and increased fluid within the medullary compartments (sometimes referred to as ''bone marrow edema''), microarchitectural or cellular detail cannot be determined with this imaging modality.…”
mentioning
confidence: 99%